If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X)(5X)(2X + -2) = 480 Remove parenthesis around (5X) X * 5X(2X + -2) = 480 Reorder the terms: X * 5X(-2 + 2X) = 480 Reorder the terms for easier multiplication: 5X * X(-2 + 2X) = 480 Multiply X * X 5X2(-2 + 2X) = 480 (-2 * 5X2 + 2X * 5X2) = 480 (-10X2 + 10X3) = 480 Solving -10X2 + 10X3 = 480 Solving for variable 'X'. Reorder the terms: -480 + -10X2 + 10X3 = 480 + -480 Combine like terms: 480 + -480 = 0 -480 + -10X2 + 10X3 = 0 Factor out the Greatest Common Factor (GCF), '10'. 10(-48 + -1X2 + X3) = 0 Ignore the factor 10.Subproblem 1
Set the factor '(-48 + -1X2 + X3)' equal to zero and attempt to solve: Simplifying -48 + -1X2 + X3 = 0 Solving -48 + -1X2 + X3 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| Y=8(2)-7 | | 6v=27-3v | | 62-w=281 | | 20x^3+32x^2=0 | | -9x+4x+18-11x=0 | | Y=10+0.75Y | | 7x+14=168 | | 78=-2(m+3)+6 | | 6n-22=8(7+4n) | | 3(x-6)=5x+18 | | -30+5r=-7(-2-7r) | | 6+b=5(b-2) | | 60+123+89+126= | | 13p=-208 | | 8y+1-8y=2 | | 2x+16=6+7x | | m-8=-4m-3 | | 1+6s=79 | | 20m^4+100m^3=0 | | 124p=878 | | 4-6b=-3-5b | | X/4-7=18 | | 5x+31+15x+9x+63=12 | | 14+3x=x+6 | | 8k-4k-5= | | 7(6n-6)=-126 | | -18=6x+6y | | 5m+4m=72m | | 8(8+p)=104 | | 5(-5+3r)=-100 | | 2.4n+3=1.8n+5.4 | | 5x+31+15x+9x+63=180 |